Perinatal outcome in relation to fetal sex in offspring to mothers with pre‐gestational and gestational diabetes—a population‐based study. Issue 9 (12th May 2014) - Persson, M.; Fadl, H.
Abstract Aim The objective of the present study was to investigate if perinatal outcome differs with fetal sex in pregnancies with maternal Type 1 diabetes, Type 2 diabetes or gestational diabetes. Methods This was a population‐based cohort study, with data from the Medical Birth Registry in Sweden throughout the period 1998–2007. Singleton pregnancies with maternal Type 1 diabetes (n = 4092), Type 2 diabetes (n = 412) and gestational diabetes (n = 8602) were identified based on the International Classification of Diseases, 10th edition code. For comparison, 905 565 pregnancies without diabetes were included. The primary outcome was a composite outcome, consisting of any of the following diagnoses: perinatal mortality rate, major malformation, preterm delivery, acute respiratory disorders and neonatal hypoglycaemia. Logistic regression was used to obtain odds ratios for adverse outcomes in male offspring within the diabetic and reference cohorts, respectively. Results In pregnancies with diabetes, maternal characteristics did not differ with fetal sex, except for a higher rate of Caesarean delivery in male offspring of women with Type 1 diabetes. Male infants to mothers with Type 1 diabetes and gestational diabetes had significantly increased odds of respiratory disorders [adjusted odds ratio (confidence interval) Type 1 diabetes: 1.50 (1.12–2.02); gestational diabetes: 1.81 (1.27–2.57)]. Male infants to mothers with gestational diabetes also had significantly increased odds of major malformations [adjusted odds ratio: 1.44 (1.07–1.93)]. In offspring of mothers with Type 2 diabetes, odds ratios of most outcomes were higher in male infants; however, not significantly different from female infants. In pregnancies without diabetes, male infants had significantly higher odds of all adverse outcomes, except perinatal mortality rate. Conclusion The risk of adverse perinatal outcome in offspring of mothers with Type 1 diabetes and gestational diabetes did not differ by sex, except for a higher risk in male infants for respiratory disorders. The risk of major malformations was also significantly increased in male offspring to mothers with gestational diabetes. In offspring of mothers with Type 2 diabetes, no significant differences between sexes were found.